The role of the magnetic component of a strong light field in the electrostrictive effect - Poperenko, L.V.; Prorok, V.V.; Rozouvan, S.G.; Shaykevich, I.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
Electrostriction forces during laser ablation have been studied both theoretically and experimentally. The components of the electrostriction force for an inhomogeneous electromagnetic field near a substrate were proposed to be taken similarly to those in gases within the nonresonant spectral region. Nonzero Lorentz force in a standing light wave was found to be responsible for the different morphology of the nanostructured surface as compared to etching the transient substrate. Our experiments were performed using the femtosecond laser focused on polished glass and Al-coated glass surfaces. The treated surfaces were studied using atomic force microscopy with a spatial resolution of 30 nm. Nanoscale patterning of the etched surface spots was explained in the framework of theoretical modeling. Possible spatial locations of electrostriction force components in the Gauss profile laser beam have also been discussed.